Formation Mechanism and Control Strategies of Haze in China - He, Hong.; Wang, Xinming; Wang, Yuesi; Wang, Zifa.; Liu, Jianguo; Chen, Yunfa (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book summarizes the new major research findings about formation mechanism and control strategies of haze in China, including basic theories, key technologies, equipment and platforms and the applications and implementations of control technologies, in implementing the Strategic Priority Research Program (Class B) of Chinese Academy of Sciences. Different types of air pollution processes experienced by the developed countries in different stages are out-breaking simultaneously in China in the recent years and resulting a new type of "haze chemistry smog" pollution, which is different from the "London smog" and the "Los Angeles photochemical smog". This book provides a useful reference for related researchers, engineers and policy-makers engaged in atmospheric pollution research, prevention and control in China and other countries.
Introduction -- Atmospheric oxidation and secondary particle formation -- Haze Source Tracing -- Numerical Model of Atmospheric Haze -- Research and Development, Industrialization, and Application of Advanced Instruments -- Multi-Pollutant Collaborative Treatment Technology and Special Equipment of Atmospheric Haze.
Keywords: Pollution; Environmental chemistry; Inorganic chemistry; Environmental sciences -- Mathematics; Cogeneration of electric power and heat; Fossil fuels; Chemical processes; Pollution; Environmental Chemistry; Inorganic Chemistry; Mathematical Applications in Environmental Science; Fossil Fuel; Process Chemistry